On dependent action of the children of senior pre-school age in group activity - Jacikevičienė, O. (Psichologija, 1984)
Cooperative interaction of the children of senior pre-school age occurring in group (pairs) activity on their own initiative has been investigated. An appraisal of the peculiarities of common programming, distribution of functions, cooperation and competition in achieving the aim is given. Some dependence of these peculiarities on the aim of activity and body of groups has been established. The results show some practical habits of common activities and poor possibilities in transferring these habits to new conditions.
Keywords: group activity; cooperation